Use of Social Media as a Public Relations Strategy during the Covid-19 Pandemic in Indonesia - Kartika Ratri (LEGAL BRIEF, 2022)
The field of Public Relations (Humas) is a field of communication carried out to establish and manage relationships with various stakeholders (stakeholders). With digitization, public relations also take advantage of the development of digital technology to establish relationships. Until the term digital public relations emerged. Since the occurrence of the Covid-19 pandemic, when the main effort to overcome the Covid-19 pandemic was to carry out physical distancing, several stakeholders such as the government, health workers, and social organizations in Indonesia have used social media in order to deal with the Covid-19 pandemic crisis. Several social media platforms such as Instagram, Twitter, to personal conversations such as Whatsapp are used. The purpose of this study is to find out how the role of the use of Social Media as a Public Relations Strategy during the Covid-19 Pandemic in Indonesia. This research method uses a meta-analysis of 9 journal articles, which will synthesize the relationship between “Digital Public Relations” and “Social Media”. Broadly speaking, "Social Media" is a "tool" used in the practice of "Digital Public Relations" which is synthesized with the findings of previous research as a theoretical basis, the practice of social media in digital public relations, and an analysis of what is happening in Indonesia over the past few years. The Covid-19 pandemic is ongoing